Ever-increasing agricultural land and water productivity: a global multi-crop analysis. (4th September 2020) - Tuninetti, Marta; Ridolfi, Luca; Laio, Francesco
Abstract: Producing more nutritious food with less resources, while preserving the natural ecosystems, is a key challenge of our society. In this paper we propose a macronutrient-based indicator of productivity, the nutrient land productivity ( NLP ), to measure the amount of calories, proteins, and fats produced per hectare of cropland. Over the period 1961−2016, we find that the global NLP has increased by 2.7–2.9% per year for calories and proteins, and between 2.1 and 4.6% for fats. However, such rates exhibit significant spatial patterns throughout the world depending on whether farmers adopted intensification (e.g. Eastern and South Asia, North America) or extensification (e.g. Sub-Saharan Africa) practices to boost nutrients production. Our outcomes, based on a production basket including 144 crops, show that cereals and pulses cultivations have been dominated by intensification practices coupled with a stable or decreasing harvested area. Conversely, for fruits and nuts cultivations extensification prevailed over intensification, while for oil crops most cultivations experienced a coupled action of the two practises. Finally, by coupling the NLP indicator with its nutrient water productivity ( NWP ) counterpart, we find that NWP has mainly changed following land patterns, with the exception of locations having undergone significant crop substitutions, namely from less toward more water demanding crops. Indeed, the transition toward perennial crops has increased the evapotranspiration demand over cultivated land by 14% on a global average.